Sex robots and personality: It is more about sex than robots. (November 2022) - Dubé, S.; Santaguida, M.; Zhu, C.Y.; Di Tomasso, S.; Hu, R.; Cormier, G.; Johnson, A.P.; Vachon, D.
Abstract: Examining the links between personality traits and attitudes toward sex robots can provide insights into who may desire such machines, and why . This online study thus examined the associations between the Big-Five, traits related to sexuality, technology, and (sexual) novelty, and people's willingness to engage with and perceived appropriateness of using sex robots in a convenience sample of 492 adults (≥18 years; 283 ciswomen, 171 cismen, and 37 non-binary and gender nonconforming individuals with access to the recruitment material on social media, the Concordia University participant pool, or flyers/word-of-mouth in the Montreal Community). Correlational analyses showed that willingness to engage with and perceived appropriateness of using sex robots were more closely related to erotophilia and sexual sensation seeking than any other traits. Mixed repeated measures ANOVAs and independent samples t -tests with Bonferroni corrections also showed that cismen and non-binary/gender nonconforming individuals were more willing to engage with sex robots and perceive their use as more appropriate than ciswomen. These findings suggest that erotophilic individuals seeking novel or more intense sexual experiences may be(come) the primary users of sex robots and influence their development. These findings are important given the growing place of technology in our intimate lives and relationships. Highlights: Sex robots exist at the crossroad of sexuality, technology, and (sexual) novelty. Personality traits can provide insights into who is interested sex robots, and why. We examined the links between personality traits and attitudes toward sex robots. Erotophilic sexual sensation seekers are more willing to engage with sex robots. Cismen and non-binary/gender nonconforming people are more willing than ciswomen.